Banking Service Mindset - Indra Sudrajat (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2025)
This article aims to increase insight and experience about service mindset in the world of banking for readers and also for the author himself. In an era of increasingly fierce business competition, banks not only compete in terms of products and rates, but also in the quality of services provided to customers. Service quality that is oriented towards customer satisfaction or a service mindset has become the key to success for many banking institutions. A service mindset-based approach in banking services is increasingly important because it improves customer experience and creates competitive added value. Quality banking services focus not only on products but also on the quality of interactions with customers. Overall.